Streptomyces species from the rhizosphere of the medicinal plant Artemisia herba-alba Asso: screening for biological activities - Djemouai, Nadjette; Meklat, Atika; Gaceb-Terrak, Rabéa; Youcef, Khadidja Oulad Hadj; Nacer, Asma; Saadi, Sid Ahmed; Saad, Somia; Verheecke-Vaessen, Carol; Bouras, Noureddine (Springer, 2022)
This work aims to study cultivable actinobacterial isolated from the rhizosphere soil of Artemisia herba-alba Asso; an important component of the Mediterranean dry steppe flora. The isolates functional attributes with respect to antifungal, in vitro growth-promotion properties and enzymatic capacities, were studied. A total of eleven cultivable actinobacterial strains were isolated and identified as Streptomyces species by 16S rRNA gene sequencing. The eleven Streptomyces strains were positive for the production of almost all the hydrolytic enzymes tested, while the majority had ACC deaminase activity (6 strains) and exhibited ammonia (7 strains), siderophores production (9 strains) and phosphate solubilization (6 strains). Two out of the eleven strains named Streptomyces sp. BKS30 and BKS40 showed antifungal activities. One promising Streptomyces sp. strain BKS30 that was in-depth characterized morphologically and biochemically was further tested for its antifungal activity for the filtrate and the butanolic extract against nine target-fungi as well as for its antioxidant activity by DPPH and ABST tests. The obtained results demonstrate that Streptomyces species isolated from the rhizosphere of Artemisia herba-alba Asso have the potential for different biological activities including antifungal and antioxidant activities particularly for strain BKS30.
Keywords: Rhizosphere; Streptomyces; Artemisia herba-alba; Antifungal; Antioxidant; Plant growth-promoting traits